Kat Kong : starring Flash, Rabies, and Dwayne and introducing Blueberry as the Monster - Pilkey, Dav, 1966- (Harcourt, 1993)
Doctor Varmint and his beautiful assistant, Rosie Rodent, have made--and captured--a stunning scientific discovery: the mighty Kat Kong. But when he breaks free from his shackles and tears through the streets of Mousopolis, there's no stopping his terrifying rampage. Is anyone clever enough to halt this massive meowing menace?